Keyword spotting system for broadcast news - ZHANG Peng-yuan; SHAO Jian; ZHAO Qing-wei; YAN Yong-hong (Tongxin xuebao)
A two-step keyword spotting strategy was presented.This strategy allowed to change keyword list conven-iently.Different from the previous systems,search space was generated based on all Chinese syllables,not specifically for keywords.Phoneme recognition was performed without any lexical constraints.With 1-best phoneme sequence and keyword list,which generated keyword hypotheses.At last,two confidence measures were introduced adopted in the sys-tem: one based on acoustic model and the other based on phoneme lattice.For a decoded speech frame aligned to an HMM state,the acoustic confidence was calculated.The lattice confidence made use of phoneme lattices generated by a phoneme recognizer.These two confidence measures were combined using a weighting factor to obtain a hybrid confi-dence as they had different dynamic scales.Experiments show that the proposed algorithms significantly improve the system performance on the broadcast news task.